The Montreal General Hospital Pain Centre (1974-2000): The Contributions of Ronald Melzack - Mary Ellen Jeans; Joseph Stratford; Paul Taenzer; Sandra Lefort; Kathleen Rowat (Pain Research and Management)
This paper chronicles the development of the Montreal General Hospital Pain Centre from its inception in 1974 to the present. Highlighted in particular are the contributions of Ronald Melzack to this history. Data for the article arose, in the main, from an interview with Dr Melzack carried out earlier in the year. Discussions with former and present members of the pain centre team, including former graduate students, provided additional information. The article begins with a recounting of those individuals and events that inspired Ron early in his 'pain career' to pursue his dream of a multidisciplinary pain centre, the first of its kind in Canada. The forces that helped shape the development of this centre and the challenges that had to be overcome are described.